2009
DOI: 10.1002/14651858.cd006085.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antiamoebic drugs for treating amoebic colitis

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 118 publications
0
36
0
Order By: Relevance
“…In this study, our findings demonstrated the efficacy of 10 day course of Metronidazole in resolving diarrhea for which the causative organism was identified by microscopic examination of stool samples to be Entamoeba histolytica, so Metronidazole which is an amoebicidal and bactericidal agent with low toxicity is the drug of choice to treat acute amoebic colitis and it is found that Metronidazole is effective against amoebic liver abscess (McAuley et al, 1992;Gonzales et al, 2009), although surgical aspiration may be needed sometime, but it is demonstrated that use of another agent in addition to Metronidazole that is active against cysts is needed in some cases like Septrin which has efficacy rate of more than 90% in eradication of the amoebic cysts (McAuley et al, 1992), but the use of this agent is limited because of its adverse effects (Gastrointestinal and neurological side effects which were produced in 9% of the patients given the treatment after 14 years experience with the use of Septrin. The clinical syndrome of non-dysenteric intestinal amoebiasis or chronic amoebiasis has been a controversial entity for sometime.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, our findings demonstrated the efficacy of 10 day course of Metronidazole in resolving diarrhea for which the causative organism was identified by microscopic examination of stool samples to be Entamoeba histolytica, so Metronidazole which is an amoebicidal and bactericidal agent with low toxicity is the drug of choice to treat acute amoebic colitis and it is found that Metronidazole is effective against amoebic liver abscess (McAuley et al, 1992;Gonzales et al, 2009), although surgical aspiration may be needed sometime, but it is demonstrated that use of another agent in addition to Metronidazole that is active against cysts is needed in some cases like Septrin which has efficacy rate of more than 90% in eradication of the amoebic cysts (McAuley et al, 1992), but the use of this agent is limited because of its adverse effects (Gastrointestinal and neurological side effects which were produced in 9% of the patients given the treatment after 14 years experience with the use of Septrin. The clinical syndrome of non-dysenteric intestinal amoebiasis or chronic amoebiasis has been a controversial entity for sometime.…”
Section: Discussionmentioning
confidence: 55%
“…The present recommendations are to combine this drug with some luminal amoebicidal like paromycin or diloxanide furoate. Though metronidazole is effective in treating the amoebiasis but it resulted in failure due to development of resistance by E. histolytica against it (Orozco, 2002;Gonzales, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Tinidazole and ornidazole are further alternatives to metronidazole in the treatment of amoebiasis, giardiasis and trichomoniasis [79][80][81][82]. Tinidazole is administered in a 2 g dose taken daily over 3 days for intestinal amoebiasis in adults, and in children at 50 M a n u s c r i p t A c c e p t e d M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t A c c e p t e d M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t…”
Section: Amoebiasis Giardiasis and Trichomoniasismentioning
confidence: 99%